13.6k views
4 votes
You have two exponential functions. One function has the formula g(x) = 5 x . The other function has the formula h(x) = 5-x . Which option below gives formula for k(x) = (g - h)(x)?

k(x) = 10x
k(x) = 5x + 5-x
k(x) = 5x - 5-x
k(x) = 2(5x)

User Moin
by
5.3k points

2 Answers

5 votes
Hmm it would be k(x)=2(5x) or it could be k(x)=10x

Hope this helps!
User Ryan Duffield
by
5.6k points
6 votes

g(x) = 5x

h(x) = 5 - x

k(x) = (g - h)(x)

k(x) = g(x) - h(x)

k(x) = 5x - (5 - x)

Hence, the correct option is k(x) = 5x - 5-x


User Jon Heller
by
6.0k points